Breast intraductal papillomas without atypia in radiologic‐pathologic concordant core‐needle biopsies: Rate of upgrade to carcinoma at excision. Issue 18 (17th June 2016) - Pareja, Fresia; Corben, Adriana D.; Brennan, Sandra B.; Murray, Melissa P.; Bowser, Zenica L.; Jakate, Kiran; Sebastiano, Christopher; Morrow, Monica; Morris, Elizabeth A.; Brogi, Edi
Abstract : BACKGROUND: The surgical management of mammary intraductal papilloma without atypia (IDP) identified at core‐needle biopsy (CNB) is controversial. This study assessed the rate of upgrade to carcinoma at surgical excision (EXC). METHODS: This study identified women with a CNB diagnosis of intraductal papilloma without atypia or carcinoma at a cancer center between 2003 and 2013. Radiologic‐pathologic concordance was assessed for all cases, and discordant cases were excluded. The radiologic and clinicopathologic features of patients with a CNB diagnosis of IDP were correlated with an upgrade to carcinoma at EXC. RESULTS: The study population consists of 189 women with 196 IDPs; 166 women (171 IDPs) underwent EXC. The upgrade rate was 2.3% (4 of 171). The upgraded lesions were 2 invasive lobular carcinomas and 2 cases of ductal carcinoma in situ (DCIS). One case of DCIS involved the residual IDP, whereas the other 3 carcinomas were ≥ 8 mm away. Twenty‐four women (25 IDPs) did not undergo EXC and had stable imaging on follow‐up (median, 23.5 months). CONCLUSIONS: The upgrade rate at EXC for IDPs diagnosed at CNB with radiologic‐pathologic concordance was 2.3%. These findings suggest that observation is appropriate for patients with radiologic‐pathologic concordant CNB yielding IDP, regardless of its size. Cancer 2016. © 2016 American Cancer Society . Cancer 2016;122:2819–2827. © 2016 American Cancer Society Abstract : The rate at which intraductal papillomas without atypia constituting the most serious finding in radiologic‐pathologic concordant core‐needle biopsy specimens are upgraded to carcinoma at surgical excision is low. Radiologic follow‐up is appropriate management for these patients.